From Analogue to Image Retrieval: Concepts of Archival Art in Daniel Blaufuks - Camacho, Sandra Gonçalves (2021)
From Analogue to Image Retrieval: Concepts of Archival Art in Daniel Blaufuks, seeks to explore a question first triggered by the viewing of Daniel Blaufuks’s Constellation series in his exhibition-project, All the Memory of the World, part one (2014): might digital databases and image retrieval systems be viewed as developments of archival processes and thinking? Has the touted rupture between analogue and digital occurred, or does archival art live in them both? With a career that spans several decades, Blaufuks has been deeply engaged with questions surrounding the Holocaust, exile, memory and postmemory. Photography, film and archival material have been the tools chosen for his excavations; nonetheless, it is impossible to overlook the influence of literature in the artist’s work. Having begun with the appropriation of physical archival material, such as photographic albums, polaroids or slides, Blaufuks has also employed digital images and image-retrieval systems such as Google Image. In the view to proceed with an analysis on the crucial argument of this thesis, I have divided it into to three sections. The first, Daniel Blaufuks: The ‘Material’ Archive, as the name indicates, focuses on considerations on the so-called material archive, meaning the analogue archive. Daniel Blaufuks: Writing with Images, the second section, is devoted to two thematic components of the artist’s oeuvre: memory and literature. Here I equally offer a comparative analysis between Blaufuks and the works of writers Georges Perec and W. G. Sebald. In Daniel Blaufuks: Traversing the Archive, the final section, I return to the theoretical frameworks surrounding the archive, yet one founded on 0s and 1s rather than paper and ink. In writing From Analogue to Image Retrieval: Concepts of Archival Art in Daniel Blaufuks, I strive to illuminate the continuities from analogue to digital archives, and analogue to digital archival art practices. Blaufuks’s ease and breadth in the incorporation of a variety of media into his projects stands as an ideal case study for the exploration of the questions I put forward in this thesis.